2015
DOI: 10.1002/jhm.2351
|View full text |Cite
|
Sign up to set email alerts
|

The highest utilizers of care: Individualized care plans to coordinate care, improve healthcare service utilization, and reduce costs at an academic tertiary care center

Abstract: BACKGROUND: High utilizers are medically and psychosocially complex, have high rates of emergency department (ED) visits and hospital admissions, and contribute to rising healthcare costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 11 publications
(13 reference statements)
1
53
0
Order By: Relevance
“…Six and 12 months after the implementation of individualized plan of service, hospital admissions decreased by 56% (p<0.001) and 50.5% (p=0.003), respectively (8). Thirty-day readmissions decreased by 66% (p<0.001) at 6 months and 51.5% (p=0.002) at 12 months after care-plan implementation (8). Limitations of this study include its small sample size and the generalizability of the data to psychiatric patients given the studied patients were not on psychiatric units when the treatment plan was formulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six and 12 months after the implementation of individualized plan of service, hospital admissions decreased by 56% (p<0.001) and 50.5% (p=0.003), respectively (8). Thirty-day readmissions decreased by 66% (p<0.001) at 6 months and 51.5% (p=0.002) at 12 months after care-plan implementation (8). Limitations of this study include its small sample size and the generalizability of the data to psychiatric patients given the studied patients were not on psychiatric units when the treatment plan was formulated.…”
Section: Discussionmentioning
confidence: 99%
“…One study evaluated the effect of individualized plan of service and the rate of hospital admissions and readmissions in 24 medically and psychosocially complex patients with high health care utilization. Six and 12 months after the implementation of individualized plan of service, hospital admissions decreased by 56% (p<0.001) and 50.5% (p=0.003), respectively (8). Thirty-day readmissions decreased by 66% (p<0.001) at 6 months and 51.5% (p=0.002) at 12 months after care-plan implementation (8).…”
Section: Discussionmentioning
confidence: 99%
“…Based on available case report data, it is anticipated that this intervention is a cost-effective initiative that will reduce ED visits and hospital admissions through enhanced care coordination. 28,29 Long-term follow-up of patients post-TIP to evaluate health system use is in progress. The TIP model achieves synchronous connection of patients with multimorbidity and their PCPs in an interprofessional case consultation focused on what is most important to the patient.…”
Section: S61mentioning
confidence: 99%
“…They found that 23 (96%) were either addicted to drugs or mentally ill, and 20 (83%) suffered from chronic pain. 4 Drug abuse among high users is becoming even more relevant as the opioid epidemic worsens. Given that most patients requiring high levels of care suffer from chronic pain and many of them develop an opioid addiction while treating their pain, physicians have a moral imperative to reduce the prevalence of drug abuse in this population.…”
Section: ■ What Drives High Costs?mentioning
confidence: 99%